2013
DOI: 10.1002/jgra.50604
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous traveling convection vortex events and Pc1 wave bursts at cusp latitudes observed in Arctic Canada and Svalbard

Abstract: [1] Traveling convection vortices (TCVs), which appear in ground magnetometer records at near-cusp latitudes as solitary~5 mHz pulses, are a signature of dynamical processes in the ion foreshock upstream of the Earth's bow shock that can stimulate transient compressions of the dayside magnetosphere. These compressions can also increase the growth rate of electromagnetic ion cyclotron (EMIC) waves, which appear in ground records at these same latitudes as bursts of Pc1 pulsations. In this study we have identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…A statistical study of TCV / Pc 1 burst events by Posch et al . [, also manuscript in preparation, 2013] found that although TCV events could be identified in ground magnetometer data up to 6 h before local noon, Pc 1 bursts associated with these TCV events were only observed within 3 h of local noon.…”
Section: Observations In the Western Greenland Sectormentioning
confidence: 99%
See 3 more Smart Citations
“…A statistical study of TCV / Pc 1 burst events by Posch et al . [, also manuscript in preparation, 2013] found that although TCV events could be identified in ground magnetometer data up to 6 h before local noon, Pc 1 bursts associated with these TCV events were only observed within 3 h of local noon.…”
Section: Observations In the Western Greenland Sectormentioning
confidence: 99%
“…stations is not surprising, however, both because of their somewhat lower latitude, and because of their local time, roughly 4.5 h before local noon. A statistical study of TCV / Pc 1 burst events by Posch et al [2011Posch et al [ , also manuscript in preparation, 2013 found that although TCV events could be identified in ground magnetometer data up to 6 h before local noon, Pc 1 bursts associated with these TCV events were only observed within 3 h of local noon.…”
Section: Observations In the Western Greenland Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that compression of the magnetosphere due to transient phenomena can cause EMIC waves [e.g., Anderson et al, 1992;Anderson and Hamilton, 1993;Engebretson et al, 2002;Usanova et al, 2010Usanova et al, , 2012Cho et al, 2016;Park et al, 2016;Saikin et al, 2016]. TCV events, which are closely associated with compression and decompression of the magnetosphere due to sudden P d change, also contribute to generation of EMIC waves [e.g., Arnoldy et al, 1988Arnoldy et al, , 1996Engebretson et al, 2013;Posch et al, 2013]. This paper presents simultaneous observations of TCVs and EMIC waves in association with transient P d changes in the magnetosphere.…”
Section: Introductionmentioning
confidence: 79%